2019
DOI: 10.1016/j.cmet.2018.12.019
|View full text |Cite
|
Sign up to set email alerts
|

ACOT12-Dependent Alteration of Acetyl-CoA Drives Hepatocellular Carcinoma Metastasis by Epigenetic Induction of Epithelial-Mesenchymal Transition

Abstract: Highlights d Down-regulation of ACOT12 is correlated with metastasis and poor prognosis of HCC d ACOT12 functionally suppresses HCC metastasis d ACOT12 regulates acetyl-coA metabolism and histone acetylation d Down-regulation of ACOT12 promotes HCC metastasis by epigenetic induction of TWIST2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 47 publications
6
86
0
Order By: Relevance
“…Thus, we reintroduced an engineered PTPN13 cDNA (coding sequence without the 3'untranslated region (3'-UTR)) that was not sensitive to shPTPN13 #4, and found that PTPN13 re-expression was a good way to test its antitumor effect. Finally, we found that reintroducing shOE-PTPN13 returned the increases in cell proliferation close to baseline levels in HCC cells, as other studies have shown [38,39]. In addition, PTPN13 has been widely suggested to have intrinsic phosphatase activity; however, this interaction was phosphatase-independent.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, we reintroduced an engineered PTPN13 cDNA (coding sequence without the 3'untranslated region (3'-UTR)) that was not sensitive to shPTPN13 #4, and found that PTPN13 re-expression was a good way to test its antitumor effect. Finally, we found that reintroducing shOE-PTPN13 returned the increases in cell proliferation close to baseline levels in HCC cells, as other studies have shown [38,39]. In addition, PTPN13 has been widely suggested to have intrinsic phosphatase activity; however, this interaction was phosphatase-independent.…”
Section: Discussionsupporting
confidence: 79%
“…Here, we found that HBx downregulated PTPN13 expression in hepatoma cells. The DNA hypermethylation of CpG islands is a critical epigenetic change that occurs in several malignancies, including HCC [39]. Aberrant PTPN13 hypermethylation has been observed in HCC [22].…”
Section: Discussionmentioning
confidence: 99%
“…Cytosolic and nuclear acetyl-CoA levels are maintained by four metabolic pathways: (1) direct synthesis from acetate and CoA via acetyl-CoA synthetase short-chain family (ACSS); (2) conversion from citrate to acetyl-CoA by ATP citrate lyase (ACLY); (3) its catabolism to acetate and CoA by acyl-CoA thioesterase (ACOT); and (4) irreversible carboxylation from Acetyl-CoA to malonyl-CoA by Acetyl-CoA carboxylase (ACC) [9]. Deregulation of acetyl-CoA has been reported in multiple cancers [23][24][25][26][27][28][29][30][31][32][33], and it contribute to malignant phenotypes.…”
Section: Acetyl-coamentioning
confidence: 99%
“…Increased Acetyl-CoA triggers metastasis by inducing histone acetylation, leading to an open chromatin permissive for gene expression. Acetyl-CoA was shown to be involved in hepatocellular carcinoma (HCC) metastasis [24]. ACOT12, which catabolizes acetyl-CoA, was silenced in HCC and associated with metastasis and poor prognosis [24].…”
Section: Acetyl-coamentioning
confidence: 99%
“…Metabolites like lactate could act as a direct signal instructing CAFs to produce HGF for tumors to survive the killing effect of sorafenib [57]. Recent studies also report that lactate and acetyl-CoA could act as substrates for histone modifications that epigenetically promote EMT and M2 polarization under hypoxia [80,81]. On the other hand, metabolic enzymes also have a direct role in regulating transcription and translation in response to hypoxia and sorafenib treatment [45].…”
Section: Metabolic Changes and Post-translational Modificationsmentioning
confidence: 99%